A Reconnaissance Study of Rare Earth Elements Systematic in Phosphate Coprolites: Comparison between Continental Shelf and Intracontinental Basin Deposits - Al-Bassam, Khaldoun S. (Iraqi Journal of Science, 2022)
The behavior of rare earth elements (REE) in phosphate coprolites; deposited in marine upwelling shelf system (Iraq) and a condensed section of the intracontinental basin (Czech Republic) is compared and discussed in the present study. The eight coprolite samples show that the REE incorporated in the apatite of these phosphatized faecal trace fossils have significantly different behavior in the two sedimentary regimes and hold the REE source’s signature in the local sedimentary conditions. The behavior of heavy REE, light REE, Ce-anomaly and shale-normalized ratios of Ce/La, Sm/Yb and Pr/Ce can be mainly attributed to REE fractionation at the source. In contrast, middle REE enrichment may be attributed to local fractionation below the sediment-water interface. Nd/La and REE/P2O5 ratios indicate local sedimentation rate and residence time in contact with seawater. Elevated La/Yb ratios indicate shallowing and submarine reworking events. Most of the REE patterns in the studied coprolites were acquired in the early stages of diagenetic phosphatization and crystallization of the apatite, and minor modifications took place later. The REE behavior in phosphate coprolites proved useful indicators of marine sedimentary environments in the present reconnaissance study and encourage further work on phosphate coprolite samples from other world deposits.